2018
DOI: 10.1097/ccm.0000000000002751
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and Psychological Distress Among Pediatric Critical Care Physicians in the United States*

Abstract: Burnout is high among pediatric critical care physicians in the United States. About two thirds of the physicians with severe burnout met the screening criteria for psychological distress that suggests possible common mental disorders. Significant percentages of physicians experiencing burnout and considering to leave the profession has major implications for the critical care workforce.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
86
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(91 citation statements)
references
References 39 publications
3
86
2
Order By: Relevance
“…33 A recent study of pediatric intensivists identified that the risk of burnout was two times greater in women than men, especially in the emotional exhaustion domain, and that regular physical activity appeared to be protective. 34 We postulate that the additional work-life integration challenges experienced by women may result in less time for self-care and reduced resilience. In addition, women physicians are often paid less 35 and experience greater work culture challenges.…”
Section: Discussionmentioning
confidence: 99%
“…33 A recent study of pediatric intensivists identified that the risk of burnout was two times greater in women than men, especially in the emotional exhaustion domain, and that regular physical activity appeared to be protective. 34 We postulate that the additional work-life integration challenges experienced by women may result in less time for self-care and reduced resilience. In addition, women physicians are often paid less 35 and experience greater work culture challenges.…”
Section: Discussionmentioning
confidence: 99%
“…A 2017 survey of 15,000 physicians from 29 specialties found that burnout was self-reported by 48 percent of women physicians and 38 percent of men physicians [17]. Smaller specialtyspecifi c studies have also found that women are more likely to exhibit burnout symptoms than are men [18,19]. Regarding trainees, a large national sample of internal medicine residents found that women physicians were more likely than men physicians to report being burned out and dissatisfi ed with work-life integration [20].…”
Section: Prevalencementioning
confidence: 99%
“…Female physicians face multiple challenges not experienced by their male counterparts. 3 In a survey 4 exclusively involving intensive care unit physicians, female (vs male) intensivists reported less career satisfaction, increased worklife integration challenges, more frequent and severe burnout symptoms, and greater incivility, echoing findings published by others. 5 Another study 3 showed heightened emotional exhaustion among female paediatric intensivists compared with men.…”
Section: Unconscious Bias In the Selection And Interpretation Of Datamentioning
confidence: 71%